The Students’ Strategy in Learning Indonesia Vocabulary at SDN 15 Pantai Hilir Labuhan Batu - Asmuri, Ali; Erix Hutagaol; Maradona Harahap; Rahma ritonga; Rahmaidani Siregar; Lili Kurniati; Maratimbo Harahap; Anna deriana Rambe; Arika Ritonga; Sri bunga; Ade mayrika Hutagalung (International Journal of Educational Research Excellence (IJERE), 2025)
The vocabulary learning strategy used, analysis repetition strategy implementation, examined effectiveness on vocabulary retention, and formulated an adaptive model for local contexts. Using a qualitative case study approach, data were collected from one primary informant and three supporting informants through interviews, observations, document analysis, and stimulated recall sessions. The analysis revealed that the primary informant developed a sophisticated multi – modal repetition system with four techniques: temporal spacing, multi – modal reinforcement, contextual variation, and self-testing. Development factors included prior learning experience, parental influence, teacher methodology, and assessment patterns. This research gaps in the literature by examining vocabulary learning in rural coastal schools, adaption of repetition strategies to local contexts, and integration of traditional strategies with innovative elements under limited technological resources. These findings contribute to the development of more inclusive vocabulary learning models for diverse educational contexts in Indonesia